Anatomical and Hemodynamic Evaluation of Mitral Stenosis Patients with Echocardiography - Muhammad Mukti; Erwin Sukandi; Ali Ghanie; Taufik Indrajaya; Syamsu Indra (HM Publisher, 2021)
Mitral stenosis (MS) is the most common valvular heart disease encountered in developing countries. The cause of MS is almost always chronic rheumatic heart disease. Echocardiography is the single most important diagnostic tool in the evaluation of MS. The objectives are to confirm the etiology, to assess the severity of stenosis, to recommend the type and timing of intervention, to assess other valvular lesions, presence of thrombus, and vegetation. According to current guidelines and recommendations for clinical practice, the severity of MS should not be defined by a single value but rather be assessed by a multimodality approach that determines valve areas, mean Doppler gradients, and pulmonary arterial pressures. The European Society of Echocardiography/American Society of Echocardiography (EAE/ASE) recommendations of measurement method for clinical practice were categorized into three level of recommendations. Mitral valve area (MVA) can be assessed by planimetry using either 2D or 3D imaging, pressure half-time (PTH), the continuity equation, and the proximal isovelocity surface area (PISA) method. These result echocardiographic examinations can increase the accuracy and appropriate management with a good prognosis.